The Influence of Social Media Usage on Loyalty with Customer Satisfaction & Brand Trust as Mediation Variable - Nugraha, Meisyitah Dwi; Dwita, Vidyarini (Banking & Management Review, 2022)
This study aims to determine (1) the effect of social media usage on customer satisfaction on wardah products. (2) The effect of social media usage on Brand Trust on Wardah products. (3) Influence of Customer Satisfaction on Customer Loyalty of Wardah products. (4) The effect of Brand Trust on @wardahbeauty Instagram customer loyalty. (5) The effect of social media usage on Wardah product customer loyalty. (6) The effect of social media usage on customer loyalty mediated by customer satisfaction. (7) The effect of social media usage on customer loyalty with brand trust as media. The population in this study were all followers of Instagram @wardahbeauty and the sample in this study were users of wardah products with a minimum of one purchase. The number of samples in this study were 131 respondents. The data in this study were collected through the distribution of online questionnaires and data processing was carried out using the SmartPLS software. The results of this study indicate that (1) social media usage has a positive and significant effect on customer satisfaction. (2) social media usage has a positive and significant effect on Brand Trust. (3) Customer satisfaction on brand loyalty has a positive and significant influence. (4) Brand Trust has a positive and significant relationship with Customer Loyalty. (5) Social media usage does not have a significant effect on Customer Loyalty.(6) Social media usage has a positive and significant relationship to customer loyalty with customer satisfaction as a mediation.(7) Social media usage has a positive and significant relationship to customer loyalty with brand trust as a mediation.